Evaluation of Healthcare Students' Knowledge on Antibiotic Use, Antimicrobial Resistance and Antimicrobial Stewardship Programs and Associated Factors in a Tertiary University in Ghana: Findings and Implications - Israel Abebrese Sefah; Emmanuel Akwaboah; Emmanuel Sarkodie; Brian Godman; Johanna Caterina Meyer (MDPI AG, 2022)
Antimicrobial resistance (AMR) is a major public health problem globally, and Ghana is no exception. Good knowledge regarding antibiotic use, AMR, and the concept of antimicrobial stewardship (AMS) is critical among healthcare students to curb rising AMR rates in the future. Consequently, a need to ascertain this. A cross-sectional survey was undertaken among fifth-year pharmacy, medical students and fourth (final)-year nursing and physician assistantship students at the University of Health and Allied Sciences in Ghana to assess their knowledge on antibiotic use, AMR and AMS using a web-based self-administered structured questionnaire. Descriptive statistics, Fishers' exact test, and multiple logistic regression analyses were performed. A total of 160 healthcare students were interviewed, of which 56.3% (n = 90) were male and 58.8% (n = 94) were in their fourth year of study. Good knowledge of antibiotic use, AMR, and AMS was associated with the study course (p = 0.001) and the number of years of study (p < 0.001). Overall, there were differences in the level of knowledge of antibiotics among the different healthcare students and their years of study. Efforts must now be made to enhance the curricula to ensure an improved and uniform transfer of knowledge of antibiotics, AMR, and AMS among the different healthcare students to sustain the fight against AMR in Ghana given growing concerns.